HUBUNGAN STATUS IMUNISASI DAN PENCEMARAN UDARA DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS TOLANGOHULA KABUPATEN GORONTALO - Dewi Modjo; Lenny Ali (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The immunization activities conducted every month, while the problem is the implementation of immunitation in the social health centers of Tolangohula has not been achieved with UCI (Universal Child immunization). The purpose of the this research was to determinate the relationship of immunization and air pollution with the incedence of ISPA to baby in the social health centers of Tolangohula.The analiyze of the data that used in this research is the analiysis of univariate anad analiysis of bivariate. Based on the results of this research concluded that (a) the immunization status and air pollution related with the incidence of ISPA to baby in the social health centers of Tolangohula. (b) has a relationship of significant between immunization status and air pollution with incidence of ISPA to baby in the social health centers of Tolangohula.